Assessment of conditions that make habitable the public space of Colombian cities - Páramo, Pablo; Burbano Arroyo, Andrea Milena (Universidad del Rosario, 2013)
This paper presents the assessment that inhabitants of some Colombian cities did on the conditions that contribute to the livability of public space. Seven hundred and forty people, inhabitants of Yopal, Villavicencio, Valledupar, Popayán, Pereira, Pasto, Neiva, Montería, Medellín, Fusagasugá, Cúcuta, Cartagena, Cali and Bogotá participated in the study. The assessment of the conditions that contribute to the livability of public space was carried out using an instrument composed of 48 items that inquired about the level of contribution that can have different conditions on the quality of public space, from a scale five points ranging from: Does not contribute at all (-2) to: Contribute significantly (+2). The results show the conditions that most affect the habitability of public space in Colombia, as well as the differences between cities according to the assessment made by participants about the general state of public space in cities. Multidimensional analysis (SSA) evidence a structure that reflects the function that public space plays in people’s assessment on Colombian cities. It is discussed the implications of the findings for urban planning and management and the designed instrument is proposed as a tool to assess the quality of urban public space.